Characteristics of Scabies Patients in Pediatric Population at Dermatology and Venereolgy Polyclinic - Dwizella, Nandya; Ganeswari, Putu Ayu Dewita; Suyanto, Firly Clarissa; Wicaksono, Andrew; Tanoto, Suma Pratiwi (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2025)
Background: Scabies has affected over 200 million individuals and remains one of the most commonly encountered skin diseases in developing countries, including Indonesia, due to limited access to water, food, and infrastructure. Therefore, scabies poses a significant problem, particularly among children in Indonesia. Severe itching symptoms along with stigma and social isolation can disrupt the quality of life. Purpose: This study aims to investigate the prevalence and characteristics of pediatric patients with scabies in the local population, specifically at the Dermatology and Venereology Polyclinic of Prof. Dr. I.G.N.G. Ngoerah Denpasar Hospital. Methods: A retrospective descriptive study conducted in a cross-sectional manner. Data were obtained from the medical records of all pediatric patients diagnosed with scabies at the Dermatology and Venereology Polyclinic of Prof. Dr. I.G.N.G. Ngoerah Denpasar Hospital from January 2021 to December 2023. The outcomes sought included the number of cases, gender, age, nutritional status, parents' education level, and treatment administered. Result: This study included a total of 53 pediatric patients. The majority of patients were male, comprising 34 patients (64.2%). There were 20 children (37.7%) with normal nutritional status, 16 children (30.2%) classified as underweight, 9 children (17%) classified as overweight, and 8 children (15.1%) classified as obese. Based on parental education level, 29 parents of the patients had completed high school education (54.7%), while the remainder had completed undergraduate (37.7%) and junior high school (7.5%). A total of 52 patients (98.1%) received 5% permethrin as scabies treatment. Conclusion: This study has provided important dst.